Understanding of Diabetes among Nurses in a Teaching Hospital of Bangladesh - Siddiqui, Md Nure Alom; Sultana, Shahnaj; Khan, MMR; Rahman, MK; Islam, MN (TAJ: Journal of Teachers Association, 2018)
Objective: Diabetes mellitus is a growing public health problem in the world. Health education by health workers is a key factor in the prevention of this chronic disease. The objective of the study was to determine nurses understanding of diabetes mellitus. Methodology: This was a cross-sectional descriptive study carried out at Rajshahi Medical College hospital from August 2010 to February 2011. Registered nurses were questioned about the clinical features, diagnosis, complications and management of diabetes mellitus. The results were analyzed using appropriate statistical method. Results: A total of 86 nurses completed the questionnaire. Majorities were below 50 years and were ward nurses. About 97.7% correctly identified the definition of diabetes mellitus (p < 0.01) and 94.2% identified <7mmol/l as the fasting plasma glucose diagnostic cut off for DM. Cent percent agreed that DM is a chronic disease (p < 0.01). Polyuria (90.3%) and polydypsia (63.7%) were the commonest clinical features of DM identified. Insulin therapy was the most common form of management identified by 67.9% of the subjects. Majority (83.2%) agreed that weight reduction is useful. About two-thirds (67.2%) identified two oral hypoglycaemic drugs while 25 (22.1%) could not identify any type of insulin. Most subjects (94.7%) could correctly identify treatment for hypoglycaemia, with 7.1% of the nurses saying that insulin can be used to treat hypoglycaemic coma. The eye (82.3%) was the most common organ identified as being complicated with DM. Less than half of the nurses could identify the symptoms of diabetic ketoacidosis while about half (50.9%) of the nurses could identify at least one symptom of diabetic ketoacidosis. Conclusion: Nurses knowledge of diabetes mellitus in Rajshahi medical college hospital is good; however, there are deficits in certain aspects of diabetes management. Organization of regular diabetes educational programmes for nurses will improve these deficiencies of knowledge. TAJ 2016; 29(1): 10-15